2020
DOI: 10.1634/theoncologist.2019-0611
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Benefit from Checkpoint Inhibitors in Mismatch Repair Deficient Metastatic Colorectal Cancer: Role of Tumor Infiltrating Lymphocytes

Abstract: Background Immunotherapy with immune checkpoint inhibitors (ICIs) is highly effective in microsatellite instability–high (MSI‐H) metastatic colorectal cancer (mCRC); however, specific predictive biomarkers are lacking. Patients and Methods Data and samples from 85 patients with MSI‐H mCRC treated with ICIs were gathered. Tumor infiltrating lymphocytes (TILs) and tumor mutational burden (TMB) were analyzed in an exploratory cohort of “super” responders and “clearly” refractory patients; TILs were then evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 25 publications
5
65
0
Order By: Relevance
“… 76 Recent research by Loupakis et al demonstrated a significant correlation between a high number of TILs and clinical responses and survival benefit in a large data set of patients with MSI-H metastatic colorectal cancer treated with ICIs. 77 These clinical benefits were also consistent with another meta-analysis, indicating that TILs are associated with improved prognosis predictions for OS. 78 …”
Section: Introductionsupporting
confidence: 82%
“… 76 Recent research by Loupakis et al demonstrated a significant correlation between a high number of TILs and clinical responses and survival benefit in a large data set of patients with MSI-H metastatic colorectal cancer treated with ICIs. 77 These clinical benefits were also consistent with another meta-analysis, indicating that TILs are associated with improved prognosis predictions for OS. 78 …”
Section: Introductionsupporting
confidence: 82%
“…Despite the high clinical activity of ICIs in this population, some patients do not benefit from these treatments, and there is currently no clear explanation for these cases of primary resistance. It is noteworthy that misdiagnosis of MSI/dMMR status is responsible for a significant amount of cases with primary resistance to ICIs [ 98 , 99 ].…”
Section: Microsatellite Instability and Immune Checkpoint Inhibitomentioning
confidence: 99%
“…The immune infiltrate might be another potential predictive biomarker [52]. It is known that the immune infiltrate may differ in quantity and quality within MSI/dMMR tumors, and 16-32% of MSI/dMMR CRC exhibit low levels of T cell infiltration [15,18,53].…”
Section: Biomarkers Predictive For Ici Efficacy Among Msi/dmmr Cancermentioning
confidence: 99%